Electrochemical Deposition of Iron with Detonation Nanodiamonds - Dolmatov, Valery; Lotnikova, Kristina (New Environmentally-Friendly Materials, 2025)
This work describes the iron plating of metal (copper) surfaces in the presence of detonation nanodiamonds (DNDs). A literature and patent review on methods for obtaining iron and iron-carbon electrochemical coatings is given, indicating the disadvantages of such coatings, and a detailed description of the modes, materials, and methods used in this work. A detailed description of the properties and behavior of ferruginous diamond-containing additives in electrolytes and their difference from known additives is given. Modes of conducting the ferruginization process and their results depending on the type of nanodiamond additive are discussed. The study was conducted using a simple and environmentally friendly sulfuric acid-based iron plating electrolyte, operating at room temperature. The objective of the study is to improve the key technical characteristics of the coating process and the iron coating itself: iron yield per current, microhardness and wear resistance. The new method resulted in a 30% increase in iron current efficiency, a multiple increase in microhardness (up to 750 kg/mm²), and wear resistance (up to 4.6 times) of the iron–diamond coating. Application: restoration of worn parts of cars, heavy machinery, equipment; hardening of working surfaces of low-carbon steel parts; application of wear-resistant coatings to products with low surface hardness.